Edukasi Pentingnya Pengawas Obat Terhadap Kepatuhan Menelan Obat Penderita Tuberkulosis Paru Dikecamatan Sarudik Kabupaten Tapanuli Tengah Tahun 2025 - Manalu, Minton; Faisal, Faisal; Hariani, Muthoh (Jurnal Inovasi Global, 2025)
Community Service by the Ministry of Health, Medan Polytechnic of Nursing Diploma III Program in Central Tapanuli aims to raise awareness about the importance of the role of Medication Supervisors (PMO) in supporting patient adherence to TB therapy. Patient adherence to long-term drug therapy is a major challenge in TB management, and PMOs play a crucial role in ensuring patients take their medications regularly as prescribed. Education was provided through outreach, seminars, and training for PMOs and patients' families to enable them to become effective medication supervisors. The results of the community service showed that the majority of PMO respondents, namely 90%, met the criteria for good supervision. Based on age, most participants were aged 18–40 years (56%), with the majority being male (77%). Respondents' education varied, with 50% having a junior high school background. Pre-test results showed that 27% had good knowledge of PMOs, while after being given education in the post-test, this figure increased to 90%. Kartikasari's research [2] showed that PMOs from family members play a major role in improving medication adherence, such as motivating and directly supervising patients. It is hoped that with good supervision, patient compliance in TB treatment will increase, accelerate the healing process, and support the achievement of the National TB elimination target.